Implementasi Peran Kepemimpinan Kepala Sekolah dalam Peningkatan Kualitas Guru - Firdaus, Muhamad (Proceedings Series of Educational Studies, 2024)
Abstract : The strength of the influence of a leader in an organization gives its own impact to common progress. The purpose of this study is to study how the role of a head of school in improving the quality of teachers in their school. The method used is qualitative with a library study model. The results of this study are that school leadership has a great impact on improving the quality of teachers, because a school leader has the duties and functions of educators, managers, administrators, supervisors, leaders, innovators, and motivators.Abstrak : The strength of the influence of a leader in an organization gives its own impact to common progress. The purpose of this study is to study how the role of a head of school in improving the quality of teachers in their school. The method used is qualitative with a library study model. The results of this study are that school leadership has a great impact on improving the quality of teachers, because a school leader has the duties and functions of educators, managers, administrators, supervisors, leaders, innovators, and motivators.